Association of G-Protein-Coupled Receptors autoantibodies with vasoregulation in Post-COVID - Felix S. Seibert; Melisa Kurucay; Lea Wiemers; Ulrik Stervbo; Oliver Sander; Monika Segelbacher; Maximilian Seidel; Sebastian Bertram; Nina Babel; Timm H. Westhoff (PLoS ONE, 2026)
Background The Post-COVID syndrome is associated with the generation of autoantibodies to vasoregulative G-protein coupled receptors (GPCR). It remains elusive, however, whether these autoantibodies play a pathophysiological role in this disease. The present study investigates whether detection and concentration of GPCR autoantibodies are related to vascular function in patients with Post-COVID. Materials and methods We performed a cross-sectional study, enrolling 80 patients with Post-COVID and 54 individuals with a history of SARS-CoV-2 infection without persisting symptoms (control group). ELISA measurement of GPCR autoantibodies encompassed autoantibodies to Angiotensin-II-Receptor-1 (AGTR2), Beta-1 Adrenergic Receptor (ADRB1), Beta-2 Adrenergic Receptor (ADRB2), Endothelin Receptor (EDNRA), Muscarinergic Choline Receptor 3 (CHRM3), and Muscarinergic Choline Receptor 4 (CHRM4). Endothelium-dependent vasodilation was assessed by flow mediated dilation (FMD). Measurement of central aortic blood pressure and capillary nailfold capillary microscopy were performed as additional assessments of vasoregulatory function. Lipoprotein-associated phospholipase A2 (Lp-PLA2) served as markers of vascular inflammation. Results 52 (65%) patients with Post-COVID had positive autoantibody findings above previously established cut-off values, the incidence was lower in the non-Post-COVID group (n = 12, 22.2%, p = 0.0001). The median concentrations for AGTR2, ADRB1, CHRM3 and CHRM4 autoantibodies were significantly higher in the symptomatic cohort (p < 0.05 each). Spearman correlation analysis showed a strong and significant negative correlation of several GPCR autoantibodies with aortic systolic blood pressure (AGTR2 p = 0.026, ADRB1 p = 0.001, ADRB2 p = 0.012) and aortic diastolic blood pressure (ADRB1 p = 0.005, CHRM4 p = 0.046) in Post-COVID. High EDNRA autoantibodies titers were associated with FMD (p = 0.038). There was no significant association of any GPCR autoantibody concentration with FMD or Lp-PLA2 in the control group. Conclusion GPCR autoantibodies were highly prevalent in this Post-COVID cohort. Several GPCR autoantibodies were associated with measures of vasorelaxation like lower systolic and diastolic aortic blood pressure and stronger endothelium-dependent vasodilation. However, given the absence of differences in microvascular and macrovascular function, the precise role of GPCR autoantibodies remains elusive.